Taphonomy of mecochirid lobsters from thelower cretaceous of west-central Argentina - Andrada, Alejandra Mariel (2022)
Lobsters of the genus Atherfieldastacus are widely distributed in the Lower Cretaceous and are usually preserved in 3D within Thalassinoides burrows or inside nodules and as laterally compressed specimens. They are commonly abundant in the outcrops where they occurred (e.g. Neto de Carvalho, 2016, Ferratges et al., 2021). At Cerro La Parva locality in the Neuquén province, west-central Argentina, thin skeletal concentrations composed mainly by glypheidean lobsters were reported by Aguirre-Urreta (1989, 1998, 2003) in two levels belonging to the Karakaschiceras attenuatum Subzone of early/late Valanginian age. Two additional decapod-bearing levels were reported in recent exploration at this locality. Studied lobsters are represented by two different species of glypheideans: abundant Atherfieldastacus rapax (Harbort) (family Mecochiridae) and only four specimens of Rectaglyphea cf. R. howardae (family Glypheidae). The aim of this work is to present the preliminary results of a taphonomic analysis of the skeletal concentrations of A. rapax including an interpretation of their genetic mechanisms and their paleobiological implications. The studied skeletal concentrations of lobsters at Cerro La Parva are recorded in a thick interval of greenish and grayish siliciclastic shales that has been identified either as the upper member of the Mulichinco Formation or the lower member of the Agrio Formation (see alternative interpretations in Aguirre-Urreta 1998 and Schwarz et al., 2011). Aguirre-Urreta (1998) had reported the presence of A. rapax in a nodular bed associated with the ammonoid Karakaschiceras attenuatum and the bivalve Panopea sp., within a 0.15 m level of hard silty shales (level P11), and a 0.8 m level consisting in a coquina with small oysters and nodules with A. rapax (level P15). Additionally, two levels of shales with small calcareous nodules (P12, P14) were recently found including scarce, isolated, in-situ decapod-bearing nodules. Levels P11 and P15 correspondto skeletal concentrations that show evidence of reworking of the lobster-bearing nodules, and level P11 have an erosive base. Levels P12 and P14 are thin nodular beds immersed in shales with sparse disposition of lobsters along strike. Study materials include those previously known from levels P11 and P15 and those collected from the two new decapod-bearing levels. They were invariably preserved in incomplete calcareous nodules. A total of 112 nodules with A. rapax were recovered in the field from these four levels (P11: n=67; P12: n=11; P14: n=10; P15: n=24), and additional material (n= 136) previously collected from the same locality but without precision of the level of collection. Taphonomic analysis included the scoring of the following attributes:completeness of the lobsters (nearly complete exoskeletons, disassociation units -sensu Hyžný and Klompmaker, 2015- or isolated carapaces), encrustation (presence, absence; type of encruster; encrusted region), and disposition of the elements (anatomical connection or not, displacement of the pleon in relation with the carapace and of the pereiopods in relation with the carapace).Specimens of A. rapax are abundant and occurred in the four studied levels. Only one specimen occurs in each nodule. They are generally preserved as articulated carapaces, pleon and different elements of the pereiopods, including from complete body fossils (32%) to dissasociation units (51%) and a few isolated elements (17%). Many specimens show a connection between the carapace and pleon (53%) or are near each other (23%), while others have their carapaces raised and separated from the pleon (23%). Nodules and lobsters are encrusted by small cementing oysters, serpulid tubes and bryozoans. Oysters and serpulids are externally attached to the exoskeletons and on the external surface of nodules at the same time in several specimens. Bryozoans were represented by the cheilostome Charixa?, and were found only on the mesial surface of a mold of the meri of two specimens. The connection between carapace and pleon in more than half of the specimens of which this relation could be seen is indicative that these samples represent corpses, but a minor portion of the specimens (23%) could be interpreted as exuviae because of the displacement of the pleon (and sometimes the pereiopods).Association of parts that are not anatomically connected in the latter and lack of disarticulation in the former suggest that there was not any reworking and that the lobsters were rapidly entombed and protected from scavengers. They might have been preserved within their own burrows. Carbonate cement precipitated rapidly around the remains during a pause in sedimentation in the early diagenetic stage. This cementation was interrupted originating the incomplete nodules with exposed elements of the lobsters. Then, the nodules were reworked and exposed on the surface, possibly by erosion caused by transgression, allowing for the encrustation by serpulids and oysters. Finally, the encrusted incomplete nodules were buried. The presence of bryozoans on the mesial surface of two meri indicates that they were probably attached in-vivo. It can be inferred that they inhabited calm waters.